Position of Dalits in Local Governance: A Discussion - Adhikari, Hari Prasad (Journal of Gurubaba, 2024)
This study examined the status of Dalits in local governance in Nepal, highlighting the persistent challenges they face despite constitutional and legal reforms. Dalits, historically marginalized in Nepal's caste system, continue to experience exclusion from meaningful participation in political and administrative processes. Although legal frameworks such as the Local Level Election Act of 2017 mandate Dalit representation, particularly in ward committees, these provisions often result in symbolic participation rather than substantive influence. The study emphasizes that while Dalit women have been elected to local governance positions, they frequently face exclusion from key decision-making bodies and are marginalized within their roles. At higher levels of governance, Dalit representation remains minimal, with few Dalit individuals occupying executive positions like mayors or deputy mayors. Caste-based discrimination within political parties further hampers the nomination of qualified Dalit candidates. Despite these legal measures, the deeply entrenched caste hierarchy continues to limit Dalits' power, leaving them dependent on upper-caste individuals and reinforcing unequal power dynamics. This research calls for comprehensive reforms that not only address legal and political representation but also challenge the sociocultural structures that perpetuate caste-based discrimination. By focusing on both the institutional barriers and societal attitudes that marginalize Dalits, the study advocates for a more inclusive and participatory local governance system. It underscores the need for a transformative approach that goes beyond tokenism to ensure that Dalits can genuinely participate and influence the decision-making processes at all levels of governance.